1995
DOI: 10.1093/jat/19.5.275
|View full text |Cite
|
Sign up to set email alerts
|

Storage Temperature Effect on the Stability of Morphine and Codeine in Urine

Abstract: Urine samples collected from one laboratory volunteer and five alleged heroin addicts are prepared (without preservatives) in 5-mL aliquots in glass culture tubes and stored at room, refrigerator, and freezer temperatures. Total morphine, total codeine, free morphine, and free codeine in these samples are analyzed at 30-day intervals for an 11-month period. Total morphine and total codeine concentration decreases are observed for all specimens in all storage conditions. For samples stored in the refrigerator a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…This issue increased the interest of toxicological laboratories to ensure that analyte instability will not affect analytical results during the retesting period. A large body of data is available on the stability in urine of phencyclidine [7][8][9], lysergic acid diethylamide [9][10][11][12][13], cannabinoids [8][9][10][11][12][13][14][15][16][17][18][19][20], morphine and codeine [8,9,17,[21][22][23][24][25][26], and cocaine/benzoylecgonine [8,10,15,17,[26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…This issue increased the interest of toxicological laboratories to ensure that analyte instability will not affect analytical results during the retesting period. A large body of data is available on the stability in urine of phencyclidine [7][8][9], lysergic acid diethylamide [9][10][11][12][13], cannabinoids [8][9][10][11][12][13][14][15][16][17][18][19][20], morphine and codeine [8,9,17,[21][22][23][24][25][26], and cocaine/benzoylecgonine [8,10,15,17,[26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…A false positive morphine in putrefied tissue due to the presence of putrefactive products has been reported [7]. A recent report on morphine conjugate stability showed that morphine glucuronides are stable for a few days [8] and controversial data exist concerning the stability of morphine in urine samples [9,10]. Buprenorphine is a recently marketed opiate and most of the published work relates either to the pharmacokinetics [11,12] or analysis [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The long-term stability of estazolam and alprazolam can be samples stored in freezer or refrigerator conditions. Degradation of total morphine in samples kept at room temperature progressed faster with unpredictable changes of the pattern of free morphine and free codeine, which is also a common ingredient in illicit morphine used to prepare heroin (Lin et al 1995).…”
Section: Stability Of Drugs and Formation Of Artefacts In Postmortem mentioning
confidence: 99%